Models for plastic flow: People, places, concepts and techniques - Mike Ashby (Journal of Materials Research and Technology)
Fred Kocks' professional life spanned a period of intense development in the understanding of the micromechanics of plastic flow. Continuum plasticity theory and the concepts of crystal plasticity with defined slip planes and directions were well established in 1959 when Fred graduated from the University of Göttingen. The concept of dislocations, discrete carriers of deformation, and their interactions, had initiated a wave of activity across Europe and the US, offering the potential for micro-mechanical models for plastic flow and its dependence on composition, temperature, time (strain-rate) and prior mechanical history. Fred became one of the principal players in the field, starting with his 1958 study of the deformation of polycrystals [1]. To understand his approach and his subsequent contributions it helps to have a picture of the intellectual climate of Göttingen and the excitement of generated by dislocation-plasticity at that time. This brief paper describes this context in which Fred's work should be viewed.